2006
DOI: 10.1159/000092609
|View full text |Cite
|
Sign up to set email alerts
|

Screening for the Formation of Reactive Oxygen Species and of NO in Muscle Tissue and Remote Organs upon Mechanical Trauma to the Mouse Hind Limb

Abstract: Background: Until now, no systematic surveys exist in the literature on the early local and systemic generation of reactive oxygen species and of nitric oxide in response to muscle crush injury. Therefore, this study aims to evaluate the formation of reactive oxygen species and nitric oxide in different tissues (injured and contralateral muscle, liver, kidney, spleen and blood) that is induced by closed muscle trauma. Methods: 5, 45 and 180 min after induction of blunt trauma to the mouse gastrocnemius muscle,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 88 publications
0
9
0
1
Order By: Relevance
“…The nitrite/nitrate levels did not differ between groups at either experimental time point (24 h or 7 days). Kerkweg et al [37] evaluated the local and systemic formation of ROS and nitric oxide at 5, 45 and 180 min after induction of blunt trauma to the mouse gastrocnemius muscle and demonstrated that local formation of ROS in injured muscle began immediately upon induction of mechanical trauma, as indicated by changes in the glutathione redox balance; nitrite levels, however, were not increased at these times.…”
Section: Discussionmentioning
confidence: 99%
“…The nitrite/nitrate levels did not differ between groups at either experimental time point (24 h or 7 days). Kerkweg et al [37] evaluated the local and systemic formation of ROS and nitric oxide at 5, 45 and 180 min after induction of blunt trauma to the mouse gastrocnemius muscle and demonstrated that local formation of ROS in injured muscle began immediately upon induction of mechanical trauma, as indicated by changes in the glutathione redox balance; nitrite levels, however, were not increased at these times.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, treadmill running-related overuse of tendon results in increased NO production, which has been suggested to play a role in the repair process (389). The induction of mechanical damage to gastrocnemius muscle resulted in increased NO formation and is believed to initiate the signaling process to damage repair (178).…”
Section: Exercise-induced Inflammation and Rosmentioning
confidence: 99%
“…22 It has been shown that the induction of mechanical damage to gastrocnemius muscle increases NO formation, which is considered to start a signaling process for damage repair. 49 In another study, it has been indicated that the concentration of NO increased throughout about 5 months of training in elite swimmers (mean aged: 21.5 years). 48 Similar variations were also observed in the salivary NO concentration and muscle injury markers such as CK.…”
Section: Discussionmentioning
confidence: 92%